Effect of plant density on the growth of the common Mallow, Malva sylvestris L. (Journal of Hama University, 2024)
This field experiment was carried out in Qutaylibiyah in Jableh countryside the during the agricultural season 2023-2024, to study the effect of plant density on the growth of the common Mallow plant, Malva sylvestris L. The seeds were planted on 1/11/2023. The experiment included four planting densities of 45 x 10 cm, 45 x 20 cm, 45 x 30 cm, 45 x 40 cm. The experiment was designed according to a completely randomized block design with three replicates for each treatment. The results showed a significant effect of plant density on all studied traits. High density achieved the highest plant height (70.35 cm), while low density achieved the highest number of branches (8.05 branches/plant), the highest number of leaves on the plant (40.20 leaves), and the highest area. Leaf size (70.25 cm2), highest root length (27.25 cm), and highest root diameter (1.51 cm).
Keywords: Mallow, plant density, spacing, growth.